The role of technology acceptance model in evaluating educational games for higher education - Mohamad Firdaus Che Abdul Rani; Nor Hafizah Adnan; Ahmad Zamri Mansor; Melor Md. Yunus (Bulletin of Electrical Engineering and Informatics, 2026)
This systematic review investigates the application of the technology acceptance model (TAM) in evaluating the acceptance of educational games within higher education. Educational games have become prominent tools for enhancing learning outcomes through interactive and engaging experiences. Guided by TAM, this review analyzes how key constructs (perceived ease of use (PEOU), perceived usefulness (PU), attitude toward use (ATU), behavioral intention (BI), and perceived enjoyment (PE) influence students’ acceptance of educational games. Using preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, relevant studies published between 2020 and 2024 were systematically identified from Scopus and Web of Science (WoS) databases, with 20 empirical studies meeting the inclusion criteria. The synthesis reveals that PU and PEOU are the most significant predictors of acceptance, while hedonic factors such as enjoyment and flow enhance engagement and sustained use. Key challenges include technical limitations, cultural misalignment, inconsistent TAM extensions, and a lack of longitudinal evidence. The review highlights the need for context-aware and inclusive design approaches that integrate both cognitive and affective factors. Overall, the findings position TAM not only as an evaluative framework but also as a design-oriented model for developing effective, engaging, and pedagogically grounded educational games in higher education.